Compound

By introducing cyclic dextrin side chains into the polymer and passing the main chain through the cyclic dextrin ring to form a movable crosslinking point, the problem of insufficient strength and elasticity of the biodegradable resin in the prior art is solved, and a high-strength and high-elastic resin is achieved.

JP2025038068AActive Publication Date: 2025-03-18OSAKA UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024217672
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-05-08
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-05-08

AI Technical Summary

Technical Problem

The prior art is difficult to improve the strength and elasticity of acrylate resin while maintaining biodegradability.

Method used

A polymer with cyclic dextrin side chains is used, whose main chain passes through the cyclic dextrin ring to form a movable crosslinking point, thereby increasing the strength and elasticity of the resin.

Benefits of technology

The biodegradable polymer has achieved significant improvements in strength and elasticity, avoiding the resin hardening and brittleness problems caused by traditional cross-linking methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a polymer comprising an aliphatic polyester resin skeleton, which combines biodegradability with superior strength performance.SOLUTION: The present invention provides a polymer having a cyclodextrin skeleton in its side chain and comprising, at least in part, a fatty acid polyester resin structure. Preferably, the fatty acid polyester resin structure is polycaprolactone. Preferably, the cyclodextrin skeleton has the structure illustrated below.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer having a cyclodextrin skeleton and an unsaturated compound. [Background technology]

[0002] Aliphatic polyesters such as polycaprolactone (PCL) are being considered as resins with low environmental impact because of their biodegradability. They are also attracting attention from the viewpoint of reuse through recycling because they can be decomposed and recombined with enzymes.

[0003] However, since the strength of aliphatic polyesters is insufficient, improvements in their physical properties are required for their widespread use. Many attempts have been made to achieve this, and crosslinking by covalent bonds, for example, has been considered. However, when crosslinking by covalent bonds is performed, the elasticity of the resin is significantly reduced, and even if the strength can be increased, the resin becomes hard and brittle, and sufficient performance cannot be obtained. For this reason, it has been difficult to obtain a resin having excellent properties in both strength and elasticity using aliphatic polyesters.

[0004] Polymer materials having a cyclic molecule cyclodextrin (CD) in the side chain are known (for example, Patent Document 2). In such polymer materials, the polymer main chain penetrates the CD ring to form crosslinks, and the crosslinks by CD perform a sliding motion when stress is applied, and show high stress dispersion. Regarding such a structure, studies have been conducted mainly on acrylic resins, but not on polyester resins.

[0005] Non-Patent Document 1 describes a polyurethane resin having a cyclic cyclodextrin in its side chain, but does not describe the modification of an aliphatic polyester resin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2019-203082 [Patent Document 2] International Publication 2022 / 024908 [Non-patent literature]

[0007] [Non-Patent Document 1] Soft Matter, 2022,18,5027-5036 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a polymer having an aliphatic polyester resin skeleton which is biodegradable and has excellent properties in terms of strength and flexibility. [Means for solving the problem]

[0009] The present invention relates to a polymer having a cyclodextrin skeleton as a side chain of the polymer and having a fatty acid polyester resin structure at least in a part thereof.

[0010] The fatty acid polyester resin structure is preferably polycaprolactone.

[0011] The cyclodextrin skeleton is [ka] (In the formula, R 1 are the same or different and each represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and R 1 20% or more of the above are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR 2 It is one of the following: x is an integer between 5 and 7 It is preferable that:

[0012] The polymer of the present invention preferably has structural units derived from a compound (A) having a functional group reactive with two isocyanate groups present in a cyclodextrin skeleton and in a structure other than the cyclodextrin skeleton, an aliphatic polyester (B), and a diisocyanate compound (C).

[0013] Compound (A) is

[0014] [ka]

[0015] (In the formula, R 1 are the same or different and each represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and R 1 20% or more of the above are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR 2 It is one of the following: x is an integer between 5 and 7 It is preferable that the compound is represented by the following formula:

[0016] The aliphatic polyester (B) is preferably a polycaprolactone having a skeleton derived from a diol compound in part. The polymer of the present invention may be obtained by polymerizing ε-caprolactone in the presence of an acrylic polymer having a cyclodextrin skeleton as a side chain of the polymer.

[0017] The polymerization of ε-caprolactone is preferably carried out further in the presence of a diol compound.

[0018] The present invention also relates to an unsaturated compound having a structure represented by the following general formula (11).

[0019] [ka] (In the formula, R 1 teeth, (A) The following general formula (12) -R 3 -NH-R 4 (12) (R 3 is an alkylene group having 3 to 20 carbon atoms, which may be linear or branched, and may have a substituent. R 4 is a structure represented by the following formula:

[0020] [ka] In the formula, R 10 represents hydrogen or a methyl group.

[0021] (a) The following general formula (13) -R 5 -NHCONH-R 6 (13) (R 5 is an alkylene group having 3 to 20 carbon atoms, which may be linear or branched, and may have a substituent. R 6 is the above R 4 (same as or (c) the following general formula (14): -R 5 -OCONH-R 6 (14) (R 5 and R 6 is the same as above.) It represents one of the following. R 2 represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, or an alkyl group having 1 to 30 carbon atoms. R c represents a group represented by the following general formula (1).

[0022] [ka] (In the formula, R 1 are the same or different, and each represents an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and R 1 20% or more of the above are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR 2 It is one of the following: x is an integer between 5 and 7 Effect of the Invention

[0023] The resin composition of the present invention is mainly composed of an aliphatic polyester skeleton which has a small environmental impact, and has both elasticity and toughness. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a diagram showing the shape of a tensile test sample. [Diagram 2] 1H NMR of SH-2-DiOH (500 MHz, 25°C) [Diagram 3] H NMR of PCL 1.5 k-diOH (500 MHz, 25 °C). [Figure 4] 13C NMR of PCL 1.5k-diOH (125 MHz, 25°C). [Diagram 5] 1H NMR of PCL 2.4 k-diOH (500 MHz, 25 °C). [Figure 6] 13C NMR of PCL 2.4 k-diOH (125 MHz, 25 °C). [Figure 7] 1H NMR of PCL 3.5 k-diOH (500 MHz, 25 °C). [Figure 8] 13C NMR of PCL 3.5 k-diOH (125 MHz, 25°C). [Figure 9] 1H NMR of PCL1.5k-γCD (2)-PU (500 MHz, 25 °C). [Figure 10] 1H NMR of PCL1.5k-γCD (5)-PU (500 MHz, 25 °C). [Figure 11] H NMR (500 MHz, 25 °C) of PCL2.4k-γCD (2)-PU. [Figure 12] 1H NMR (500 MHz, 25°C) of PCL 2.4k-γCD(5)-PU. [Figure 13] H NMR (500 MHz, 25 °C) of PCL3.5k-γCD (2)-PU. [Figure 14] H NMR (500 MHz, 25 °C) of PCL3.5k-γCD (5)-PU. [Figure 15] 1H NMR of lPCL 1.5k-PU (500 MHz, 25°C). [Figure 16] 1H NMR of lPCL2.4k-PU (500 MHz, 25°C). [Figure 17] 1H NMR of lPCL3,5k-PU (500 MHz, 25°C). [Figure 18] 1H NMR (500 MHz, 25°C) of PCL1.5k -THEED (2) -PU. [Figure 19] 1H NMR (500 MHz, 25°C) of PCL1.5k-THEED (5) -PU. [Figure 20] H NMR (500 MHz, 25°C) of PCL2.4 k-THEED (2)-PU. [Figure 21] H NMR (500 MHz, 25 °C) of PCL2.4 k-THEED (5)-PU. [Figure 22] H NMR (500 MHz, 25 °C) of PCL3.5k-THEED (2)-PU. [Figure 23] H NMR (500 MHz, 25 °C) of PCL3.5k-THEED (5)-PU. [Figure 24](a) GPC curve of PCL 1.5 k-PUs; (b) GPC curve of PCL 2.4 k-PUs; (c) GPC curve of PCL 3.5 k-PUs. [Diagram 25] ATR-FTIR of PCL 2.4 k-PUs [Figure 26] Second scan DSC curve of PCL 2.4 k-PUs [Figure 27] (a) Tg, (b) ΔH results of PCL 2.4 k-PUs from second scan DSC curves. [Figure 28] Stress-strain curves of PCL-PUs. [Figure 29] Stress-strain curves of PCL 3.5 k-PUs. [Diagram 30] Toughness and Young's modulus of PCL-PUs. [Diagram 31] Toughness and Young's modulus of PCL 3.5 k-PUs. [Diagram 32] Hysteresis loss calculated from cyclic stress-strain curves at a fixed strain (200%). Ten cycles were performed. [Diagram 33] Strain of (a) PCL1.5k-γCD (2) -PU, (b) PCL1.5k -γCD (5) -PU, (c) PCL2.4k -γCD (2) -PU, (d) PCL2.4k -γCD (5) -PU [Diagram 34] (a) Cyclic tensile test curves of PCL2.4k-γCD (5)-PU recorded with increasing maximum strain (200%, 400%, 600%, 800%, 1000%, 1200%). (b) Energy dissipation and damping capacity of each circle of the cyclic tensile test curve. [Diagram 35] (a) Cyclic tensile test curves of PCL3.5k-γCD(5)-PU recorded with increasing maximum strain (200%, 400%, 600%, 800%, 1000%, 1200%). (b) Energy dissipation and damping capacity of each circle of the cyclic tensile test curve. [Diagram 36] Stress relaxation time curve of PCL2.4k -γCD (2) -PU. [Figure 37]Stress relaxation time curve of PCL3.5k-γCD (5) -PU [Figure 38] (a) Toughness and (b) Young's modulus of the original film (n=1), the film after the first recycling (n=2), and the film after the second recycling (n=3). [Figure 39] FIG. 1 shows the results of an enzymatic decomposition reaction. [Diagram 40] FIG. 1 shows the results of an enzymatic polymerization reaction. [Diagram 41] FIG. 1 shows the results of an enzymatic polymerization reaction. [Diagram 42] Stress-strain curve of polymer using SH-02-siOH. [Diagram 43] Toughness and Young's modulus of polymers using SH-02-siOH. [Diagram 44] 1 is a schematic diagram showing a method of heat pressing, in which Teflon is a registered trademark. [Diagram 45] FIG. 2 is a diagram showing the shape of a tensile test sample. [Diagram 46] 1HNMR of Ac-γ-CD-AAm and pEAγXD_1 [Figure 47] 1H NMR of pEAγCD1_PCL50 and PCL [Figure 48] Elution curve of pEAγCD1_PCL50 [Figure 49] Stress-strain curves and the relationship between Young's modulus and breaking strength (a) and (b) are the results for MC elastomer, and (C) and (D) are the results for pEAγCD1_PCL50. [Figure 50] Stress-strain curve and relationship between Young's modulus and breaking strength of MC elastomer (pEAγCD1_PCLx (x=0.50,60,70)). [Figure 51] Stress-strain curves of (a) pEAγCD1_PCL50 and pEAγCD_1 (b) pEAγCD1_PCL50_M. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below. As described above, the polymer of the present invention has an aliphatic polyester skeleton as a main structural unit, and in order to improve its physical properties, the polymer has a cyclodextrin skeleton in the side chain. The cyclodextrin ring has excellent elastic properties because the polymer main chain penetrates its center. Furthermore, when stress is applied, the bond is not broken, and the ring structure moves along the main chain to accommodate deformation due to stress. Therefore, the physical properties are not deteriorated by the bond breaking, and it is possible to achieve both excellent elasticity and strength, which are properties that are normally difficult to achieve at the same time.

[0026] In the present invention, the polymer has a cyclodextrin ring in its side chain. Such a cyclodextrin ring preferably has a structure represented by the following general formula (1).

[0027] [ka] (In the formula, R 1 are the same or different and each represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and R 1 20% or more of the above are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR 2 Either one. x is an integer between 5 and 7

[0028] The compound represented by the above general formula (1) is preferably one in which 20% or more of the hydroxyl groups bonded to the cyclodextrin ring are substituted with hydrophobic groups. In other words, since the main skeleton of the compound is a hydrophobic aliphatic polyester resin, it is preferable that the hydroxyl groups of the cyclodextrin ring are hydrophobized, in terms of increasing compatibility and improving physical properties.

[0029] In the above general formula (1), R 160% or more of the above are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR 2 It is more preferable that the cyclodextrin ring is either one of the above, and more preferably 90% or more. The upper limit is not particularly limited, and all hydroxyl groups may be substituted. The cyclodextrin ring having a higher hydrophobicity has a better affinity with organic functional groups, and is therefore preferable in terms of having a higher affinity with aliphatic polyesters.

[0030] There are three types of dextrin skeletons: α (x=5), β (x=6), and γ (x=7). Any of these may be used, but β or γ is particularly preferred. When β or γ is used, it is particularly preferred in that the main chain is likely to have a structure that penetrates the ring. It is also acceptable to mix two or more of α, β, and γ.

[0031] The choice of which cyclodextrin structure to use is important since it affects the properties of the resulting polymer.

[0032] Generally, it is said that it is β and γ that are easy to form a penetrating structure, so it is more preferable to use these. Furthermore, according to the study by the present inventors, when the β body is used, a polymer having the best properties in terms of breaking strength, elongation, and toughness is obtained, and when the γ body is used, a polymer having the property of exhibiting a high Young's modulus is obtained.

[0033] It is not the case that one of these is superior to the other, but it is preferable to select and use an appropriate one from the viewpoint of which property is important depending on the purpose of use. Furthermore, when it is desired to obtain intermediate performance between these two, a combination of a β-isomer and a γ-isomer may be used.

[0034] In the cyclodextrin represented by the above general formula (1), a part or all of the hydroxyl groups are R 1 It may be substituted with a group. In the general formula (1), R can be at least one group selected from the group consisting of an acetyl group, an alkyl group having 50 or less carbon atoms, and -CONHR (R is a methyl group or an ethyl group). Such substitution can be carried out by a known method.

[0035] In the polymer of the present invention, the cyclodextrin skeleton is preferably contained in a proportion of 0.1 mol to 10 mol % based on the total amount of the polymer. By being contained in such a proportion, a suitable effect can be obtained. The lower limit is more preferably 0.2 mol %, and even more preferably 0.3 mol %. The upper limit is more preferably 8.0 mol %, and even more preferably 7.0 mol %.

[0036] The polymer of the present invention has an aliphatic polyester as a main structural unit. In the present invention, the polymer has a structural unit based on an aliphatic polyester as the main chain skeleton. Aliphatic polyester is known as a resin having biodegradability, and by using this as a main structural unit, a polymer with low environmental impact can be obtained.

[0037] In addition, the aliphatic polyester can be decomposed into low molecular weight compounds by enzymatic decomposition. Furthermore, the enzymatic decomposition products can be regenerated into polymers by enzymatic reaction again. Therefore, a discarded polymer can be treated by enzymatic decomposition to obtain a low molecular weight compound. Then, the polymer of the present invention can be regenerated by performing an ester bond formation reaction again on the low molecular weight compound thus recovered.

[0038] Non-Patent Document 1 discloses a polymer having a polyether as a main structural unit. By using a polyester as a main structural unit, it is preferable in that weather resistance and chemical resistance are superior to a case in which a polyol-based structure is used as the main skeleton.

[0039] Such an aliphatic polyester may be one obtained by polymerization of a hydroxycarboxylic acid or ring-opening polymerization of a lactam, or may be one obtained by polycondensation of an aliphatic dicarboxylic acid and an aliphatic diol, or may be a copolymer thereof.

[0040] Specific examples of such aliphatic polyesters include polycaprolactone, polylactic acid, poly(1,4-butylene adipate), and poly(ethylene adipate).

[0041] When the aliphatic polyester is mainly composed of polycaprolactone, it may contain a constituent unit consisting of a diol compound in part. That is,

[0042] [ka] n is a number between 1 and 29 m is 29~1 n+m≦30

[0043] Such polycaprolactone is preferred because it is easy to synthesize and both polyester terminals are hydroxyl groups.

[0044] Such polycaprolactones are H.O.R. 3 -OH The diol compound has a structural unit based on a diol compound represented by the general formula: Although there are no particular limitations on such a diol compound, for example, one having a molecular weight of 4000 or less is preferred.

[0045] Specific examples include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, triethanolamine, and N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine.

[0046] As described above, the physical properties of the polymer of the present invention are significantly different depending on whether the cyclodextrin skeleton is a β-form or a γ-form. In addition, since the polymer has an aliphatic polyester as a basic skeleton, the physical properties of the polymer are also different from those of the polymer described in Non-Patent Document 1, which has a polyether as a basic skeleton.

[0047] When the cyclodextrin skeleton is a β-form, the elongation percentage can be 500 to 10,000%. The lower limit is more preferably 1,000%, and even more preferably 1,500%. The upper limit is more preferably 5,000%, and even more preferably 3,000%.

[0048] When the cyclodextrin skeleton is a β-form, the breaking strength can be 10 to 200 MPa. The lower limit is more preferably 20 MPa, and even more preferably 30 MPa. The upper limit is more preferably 150 MPa, and even more preferably 100 MPa.

[0049] When the cyclodextrin skeleton is a β-form, the Young's modulus can be set to 10 to 100 MPa. The lower limit is more preferably 20 MPa. The upper limit is more preferably 80 MPa.

[0050] When the cyclodextrin skeleton is a β-form, the toughness is 100 to 1000 MJm -3 The lower limit is 150MJm -3 It is more preferable that the upper limit is 700 MJm -3 It is more preferable that:

[0051] When the cyclodextrin skeleton is a γ-form, the elongation percentage can be 500 to 10,000%. The lower limit is more preferably 1,000%, and even more preferably 1,500%. The upper limit is more preferably 5,000%, and even more preferably 3,000%.

[0052] When the cyclodextrin skeleton is a γ-form, the breaking strength can be set to 5 to 100 MPa. The lower limit is more preferably 10 MPa. The upper limit is more preferably 70 MPa.

[0053] When the cyclodextrin skeleton is a γ-form, the Young's modulus can be set to 20 to 200 MPa. The lower limit is more preferably 30 MPa. The upper limit is more preferably 150 MPa.

[0054] When the cyclodextrin skeleton is a γ-form, the toughness is 50 to 700 MJm -3 The lower limit is 80MJm -3 It is more preferable that the upper limit is 500 MJm -3 It is more preferable that:

[0055] Thus, the polymer of the present invention is preferable in that it can be made into a resin having excellent physical properties. Moreover, these values ​​are values ​​obtained by the measurement method in the example of the embodiment 1 in the examples of the present specification.

[0056] The present invention may be a polymer consisting of only the above-mentioned polycaprolactone structure and components for forming a cyclodextrin skeleton in the side chain, but may also have other structural units. That is, to obtain excellent strength, the following specific examples of the polymer that uses other structural units in combination are as follows: Aspect 1 and Aspect 2.

[0057] (Aspect 1) A polymer having structural units derived from a compound (A) having a functional group reactive with two isocyanate groups present in a cyclodextrin skeleton and in a structure other than the cyclodextrin skeleton, an aliphatic polyester (B), and a polyisocyanate compound (C). (Aspect 2) A polymer obtained by polymerizing ε-caprolactone in the presence of an acrylic polymer having a cyclodextrin skeleton as a polymer side chain.

[0058] In these embodiments, a resin structure other than the aliphatic polyester is introduced into the polymer in order to further improve the physical properties of the polymer. Hereinafter, such embodiments 1 and 2 will be described in detail.

[0059] (Regarding aspect 1) The polymer of embodiment 1 is a polyurethane resin having a biodegradable aliphatic polyester skeleton, to which a structure derived from compound (A) has been introduced. In such a structure, the resin chain penetrates the cyclodextrin ring to form a crosslinking point, and it is presumed that the crosslinking point by CD performs a sliding motion when stress is applied, resulting in a mobile crosslinked material that exhibits high stress dispersibility.

[0060] Furthermore, since the polymer has urethane groups, a crosslinked structure due to hydrogen bonds is also formed. Therefore, it is preferable in that the polymer achieves even better physical properties due to the synergistic effect of two types of crosslinked structures with different mechanisms, namely crosslinking due to CD and crosslinking due to hydrogen bonds.

[0061] In order to introduce a cyclodextrin skeleton into such a polymer, it is necessary to have a skeleton derived from a compound having two or more hydroxyl groups in a structure other than the cyclodextrin skeleton in addition to the cyclodextrin ring. Since such a compound (A) has a functional group that reacts with isocyanate, it can be introduced into a polymer by reacting it with a polyisocyanate compound. An example of the chemical formula of the compound obtained by such a reaction is shown below.

[0062] [ka]

[0063] In the compound of the above general formula, the aliphatic polyester (B) is a polycaprolactone having a diethylene glycol skeleton in part, the isocyanate compound (C) is tetramethylene diisocyanate, and a specific compound represented by the general formula (2) is used as the compound (A). Such a compound is one example of the polymer of the present invention, and the present invention is not limited to such a specific polymer. Each of the components (A) to (C) will be described in detail below.

[0064] (Compound (A) having a functional group reactive with the isocyanate group 2 present in the cyclodextrin skeleton and in a structure other than the cyclodextrin skeleton) Compound (A) is a compound having a cyclodextrin ring. In the polymer of the present invention, a crosslinked structure is formed by the main chain derived from another component penetrating the cyclodextrin ring of such compound (A).

[0065] Compound (A) has a cyclodextrin skeleton represented by the above-mentioned general formula (1) and further has two or more functional groups reactive with isocyanate groups. Examples of functional groups reactive with isocyanate groups include hydroxyl groups, amino groups, and carboxyl groups. These functional groups react easily with polyisocyanate compounds. Therefore, they are incorporated into the resin by the reaction of each of the components (A) to (C) described in detail below. This results in a resin having a cyclodextrin structure in the side chain of the polymer main chain. Then, the main chain penetrates through this cyclodextrin structure to form a crosslinked structure.

[0066] In the compound (A), it is necessary that there are two or more functional groups reactive with an isocyanate group. This allows the compound (A) to be incorporated into the polymer main chain, and a polymer having a cyclodextrin structure in the polymer side chain is obtained. When there are two functional groups reactive with an isocyanate group, a chain resin is obtained. When there are three or more functional groups reactive with an isocyanate group, such a compound itself becomes a crosslinking point. It is particularly preferable to use a compound having a total of two functional groups reactive with an isocyanate group, since it is easy to control the physical properties and easy to handle.

[0067] Such compounds include those having the following structures in the molecule: [ka] It is preferred that the compound has a structure represented by the following formula: Compounds having such structures are preferable in that they can be easily synthesized and produced from relatively inexpensive raw materials.

[0068] Such a compound can be obtained, for example, by reacting a compound having an unsaturated bond and a cyclodextrin structure with α-thioglycerol. That is, it can be obtained by adding α-thioglycerol to the unsaturated bond. Therefore, any compound having an unsaturated bond and a cyclodextrin structure can be converted into such a compound.

[0069] More specifically, such compounds include

[0070] [ka] (In the formula, R 1 are the same or different and each represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and R 220% or more of the above are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR 3 It is one of the following: R 3 is an alkyl chain having 1 to 20 carbon atoms which may have an amide group, an ester group, or a sulfide group in the main chain. X 1 ,X 2 are the same or different, and OH or NH2x is an integer of 5 to 7.

[0071] More specifically, it is preferable to use a compound represented by the following general formula (2).

[0072] [ka] Such compounds are known compounds described in Non-Patent Document 1 mentioned above.

[0073] In addition, a compound having a structure represented by the following general formula (4) can also be used.

[0074] [ka] (In the formula, R 1 teeth, (A) The following general formula (12) -R 3 -NH-R 4 (12) (R 3 is an alkylene group having 3 to 20 carbon atoms, which may be linear or branched, and may have a substituent. R 4 is a structure represented by the following formula: [ka] In the formula, R 10 represents hydrogen or a methyl group. (a) The following general formula (13) -R 5 -NHCONH-R 6 (13) (R5 is an alkylene group having 3 to 20 carbon atoms, which may be linear or branched, and may have a substituent. R 6 is the above R 4 (same as or (c) the following general formula (14): -R 5 -OCONH-R 6 (14) (R 5 and R 6 is the same as above.) It represents one of the following. R 2 represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, or an alkyl group having 1 to 30 carbon atoms. R c represents a group represented by the following general formula (1).

[0075] [ka] (In the formula, R 1 are the same or different, and each represents an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and R 1 20% or more of the above are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR 2 It is one of the following. x is an integer between 5 and 7 More specifically, such compounds include

[0076] [ka] (In the formula, R 1 are the same or different and each represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms) R 7 represents hydrogen or a methyl group. R 8is an alkylene chain having 2 to 20 carbon atoms) Examples include:

[0077] Such compounds are preferred because they can be synthesized relatively easily and have high purity. Furthermore, the distance between the main chain and the cyclodextrin of the obtained polymer can be appropriately controlled, so that the main chain can be designed to be easily penetrated with a high degree of freedom. It is preferable in that respect.

[0078] Such compounds can be particularly preferably used for the purposes of the present invention.

[0079] Use of the compound represented by the above general formula (4) is preferred in that the resulting polymer has particularly excellent physical properties.

[0080] Such compounds can be obtained by reacting compounds having unsaturated groups as described in WO 2022 / 024908 with α-thioglycerol.

[0081] (Aliphatic polyester (B)) In the embodiment 1, the main chain skeleton has a structural unit based on an aliphatic polyester (B). Aliphatic polyesters are known as resins having biodegradability, and by using them as a main structural unit, a polymer with low environmental impact can be obtained.

[0082] Examples of the aliphatic polyester resin (B) that can be used in embodiment 1 include those mentioned above.

[0083] The aliphatic polyester (B) as a constituent unit preferably has a number average molecular weight of 1000 to 4000. The method for measuring the number average molecular weight is the method described in the Examples.

[0084] (Polyisocyanate compound (C)) The polyisocyanate compound (C) is a well-known compound widely known in the field of resins, and any of these can be used. The polyisocyanate compound (C) is preferably a diisocyanate.

[0085] In the first aspect of the present invention, since the effect is obtained by a crosslinked structure based on a structure other than a covalent bond, a crosslinked structure based on a multifunctional structure having three or more functional groups is not necessary. However, as long as the effect of the present invention is not impaired, a crosslinked structure based on a polyfunctional structure having three or more functional groups may be used. Even when a tri- or higher functional polyisocyanate compound is used in part, the amount used is preferably 15.0 mass % or less based on the total amount of the polyisocyanate compounds.

[0086] Examples of diisocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, (o-, m-, or p-)xylene diisocyanate, methylene bis(cyclohexyl isocyanate), trimethylhexamethylene diisocyanate, cyclohexane-1,3-dimethylene diisocyanate, cyclohexane-1,4-dimethylene isocyanate, 1,5-naphthalene diisocyanate, and norbornane diisocyanate.

[0087] (Containing amount) In the present invention, the amounts of the above-mentioned components (A) to (C) are not particularly limited, but are preferably within the ranges shown below.

[0088] (Content of structural units based on compound (A) having two or more hydroxyl groups present in the cyclodextrin skeleton and in structures other than the cyclodextrin skeleton) The amount of the compound (A) is preferably 0.1 to 10% by weight based on the total amount of the compounds (A) to (C). By setting the amount within this range, the number of crosslinks in the polymer can be set within an appropriate range, which is preferable in that a polymer having required physical properties can be obtained.

[0089] The lower limit of the amount of the compound (A) is more preferably 0.7% by weight, and the upper limit of the amount of the compound (A) is more preferably 1.3% by weight, and further preferably 1.0% by weight.

[0090] (Content of structural units based on aliphatic polyester (B)) The amount of the compound (B) is preferably 85.0 to 95.0% by weight based on the total amount of the compounds (A) to (C). By setting the amount within this range, the number of crosslinks in the polymer can be set within an appropriate range, which is preferable in that a polymer having required physical properties can be obtained.

[0091] The lower limit of the amount of the compound (B) is more preferably 8.0% by weight, and the upper limit of the amount of the compound (B) is more preferably 93.0% by weight, and further preferably 90.0% by weight.

[0092] (Content of structural units based on isocyanate compound (C)) The amount of the compound (C) is preferably 1 to 10% by weight based on the total amount of the compounds (A) to (C). By setting the amount within this range, the number of crosslinks in the polymer can be set within an appropriate range, which is preferable in that a polymer having required physical properties can be obtained.

[0093] The lower limit of the amount of the compound (C) is more preferably 1.5% by weight, and the upper limit of the amount of the compound (C) is more preferably 3.0% by weight, and further preferably 4.8% by weight.

[0094] (Polymer manufacturing method) The polymer of the present invention has the above-mentioned components (A) to (C) as structural units. Such a polymer can be obtained by mixing the above-mentioned components (A) to (C) in an organic solvent solution and heating the mixture to 40 to 80°C.

[0095] In such a reaction, a catalyst may be used. The catalyst is not particularly limited, and examples thereof include N,N-dimethylcyclohexylamine, dibutyltin dilaurate, N-ethylmorpholine, bis(2,dimethylaminoethyl)ether, 2,2'-oxybis(N,N-dimethylethylamine), triethanolamine, etc.

[0096] (Properties of polymer) The polymer of the first aspect of the present invention has the above-mentioned chemical structure, and it is particularly preferable that the polymer has the following physical properties. By satisfying the following properties, the polymer can have more preferably excellent physical properties.

[0097] (molecular weight) The polymer of the present invention preferably has a number average molecular weight of 10.0 to 65.0 kDa. The polymer of the present invention preferably has a weight average molecular weight of 15.0 to 100 kDa. The molecular weight is measured according to the method described in the Examples.

[0098] (glass transition temperature) The polymer of the present invention preferably has a glass transition temperature of −50.0° C. to −60.0° C. The glass transition temperature is measured according to the method described in the Examples.

[0099] (Melting Point) The polymer of the present invention preferably has a melting point of 40.0° C. to 45.0° C. The melting point is measured according to the method described in the Examples.

[0100] (Molding method) The polymer of the present invention can be molded into a desired shape by applying a solution of the polymer onto a substrate and drying it, although the molding method is not particularly limited. The polymer of the present invention can also be molded by hot press molding.

[0101] (Aspect 2) The polymer of the second embodiment is obtained by polymerizing ε-caprolactone (the polymer obtained by this polymerization reaction may be referred to as the second polymer) in the presence of an acrylic polymer (C) having a cyclodextrin skeleton as a side chain of the polymer (hereinafter, this may be referred to as the first polymer). When a new polymerization reaction is performed in the presence of the first polymer, the first polymer and the second polymer form a structure called an interpenetrating structure, in which they are closely entangled, and this improves the physical properties.

[0102] In the present invention, the first polymer has a cyclodextrin skeleton. Since such a first polymer has a crosslinked structure due to the main chain penetrating the cyclodextrin ring, an interpenetrating structure is more preferably formed. In addition, it is presumed that a part of the polycaprolactone structure penetrates the cyclodextrin ring.

[0103] For this reason, the polymer of the present invention has physical properties which are significantly different from those of a resin mixture obtained by blending the acrylic polymer (C) with polycaprolactone, and has unique and excellent physical properties which cannot be obtained by simply blending.

[0104] (Acrylic polymer (C)) The acrylic polymer having a cyclodextrin ring in the side chain may be a known polymer, and may be, but is not limited to, a copolymer of a monomer having a cyclodextrin ring in the side chain and another unsaturated polymer.

[0105] The monomer having a cyclodextrin ring in the side chain is not particularly limited and may be any known monomer. Specifically, for example, monomers such as those described in International Publication No. 2012 / 036069 and International Publication No. 2022 / 024908 may be mentioned.

[0106] (Other radical polymerizable monomers) Other radical polymerizable monomers include those represented by the following general formula (a1):

[0107] [ka] (In formula (a1), Ra is a hydrogen atom or a methyl group, R 3 represents a halogen atom, a hydroxyl group, a thiol group, an amino group which may have one substituent or a salt thereof, a carboxyl group which may have one substituent or a salt thereof, an amide group which may have one or more substituents or a salt thereof, or a phenyl group which may have one or more substituents. Examples of the compound include compounds represented by the following formula:

[0108] In formula (a1), R 3 is a carboxyl group having one substituent, examples of the carboxyl group include a carboxyl group (i.e., an ester) in which the hydrogen atom of the carboxyl group is substituted with a hydrocarbon group, a methoxypolyethylene glycol (the number of ethylene glycol units is 1 to 20, preferably 1 to 10, particularly preferably 2 to 5), an ethoxypolyethylene glycol (the number of ethylene glycol units is 1 to 20, preferably 1 to 10, particularly preferably 2 to 5), or the like. In formula (a1), R 3 When is an amide group having one or more substituents, i.e., a secondary amide or a tertiary amide, examples of the primary amide include amide groups in which one hydrogen atom or two hydrogen atoms of the primary amide are each independently substituted with a hydrocarbon group or a hydroxyalkyl group (e.g., a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group).

[0109] Among them, in formula (a1), R 3However, it is preferable that the other radical polymerizable monomer is a carboxyl group in which a hydrogen atom is substituted with an alkyl group having 1 to 10 carbon atoms, or an amide group in which one or more hydrogen atoms are substituted with an alkyl group having 1 to 10 carbon atoms. In this case, the other radical polymerizable monomer is relatively highly hydrophobic, and copolymerization with the host group polymerizable monomer is likely to proceed. More preferably, the alkyl group as the substituent has 2 to 8 carbon atoms, and particularly preferably 2 to 6 carbon atoms, and in this case, the toughness and strength of the obtained polymer material are likely to be improved. This alkyl group may be either linear or branched.

[0110] Specific examples of the monomer represented by formula (a1) include (meth)acrylic acid, allylamine, maleic anhydride, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, N,N-dimethyl (meth)acrylamide, N,N-diethylacrylamide, N-isopropyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylamide, ethoxy-diethylene glycol acrylate, methoxy-triethylene glycol acrylate, methoxy-polyethylene glycol acrylate, styrene, etc. These can be used alone or in combination of two or more.

[0111] In the acrylic polymer used in the second aspect of the present invention, the above-mentioned structural units derived from a monomer having a cyclodextrin ring in a side chain are preferably contained in a proportion of 5 to 70% by mass of the entire polymer. By keeping it within such a range, it is preferable in that the effect of improving physical properties is significantly obtained. The lower limit is more preferably 10% by mass, and even more preferably 15% by mass. The upper limit is more preferably 65% ​​by mass, and even more preferably 60% by mass.

[0112] The polymerization method for the polymer constituting the copolymer or resin composition of the present invention is not particularly limited, and can be carried out by a general method.Specific examples include radical polymerization by heat, radical polymerization by light, anionic polymerization, cationic polymerization, etc.Among these, radical polymerization is particularly preferred.

[0113] When the radical polymerization is carried out by light, it is preferable to use a photopolymerization initiator. The photopolymerization initiator is not particularly limited, and examples thereof include acetophenone-based initiators such as 1-hydroxycyclohexyl phenyl ketone (trade name: IRGACURE184), 2-hydroxy-2-methylpropiophenone (trade name: IRGACURE1173), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, and 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one; benzoin-based initiators such as benzoin and 2,2-dimethoxy-1,2-diphenylethane-1-one; benzophenone, [4-(methylphenylthio)phenyl]phenylmethanone, 4-hydroxybenzophenone, and 4-phenylbenzophenone. Benzophenone-based initiators such as 2-chlorothioxanthone and 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone; thioxanthone-based initiators such as 2-chlorothioxanthone and 2,4-diethylthioxanthone; acylphosphine oxide-based initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide; and oxime ester-based initiators such as 1,2-octanedione, 1-[4-(phenylthio)phenyl], 2-(0-benzoyloxime), ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazoyl-3-yl]- and 1-(0-acetyloxime). The amount of the photopolymerization initiator used is preferably 0.1 to 2% by weight based on the total amount of monomers constituting the copolymer or resin composition of the present invention.

[0114] The conditions for photopolymerization are not particularly limited, and examples of the light source include a high-pressure mercury lamp, an LED lamp, and a metal halide lamp.

[0115] When the radical polymerization reaction by the thermal reaction is carried out, it is preferable to use a radical polymerization initiator. The radical polymerization initiator is not particularly limited, and azobisisobutyronitrile (AIBN), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropionate) dimethyl, 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, cumene hydroperoxide, etc. can be used. The amount of the thermal polymerization initiator used is preferably 0.1 to 2% by weight based on the total amount of the monomers constituting the copolymer or resin composition of the present invention.

[0116] (Polycaprolactone Polymerization) The polymer of the present invention is obtained by polymerization of ε-caprolactone in the presence of the above-mentioned acrylic polymer (C). The polymerization of ε-caprolactone can be carried out by dissolving the raw material ε-caprolactone in an organic solvent solution of the acrylic polymer (C), by removing the solvent and impregnating the acrylic polymer (C) formed into a predetermined shape with raw materials such as ε-caprolactone, by dissolving the acrylic polymer in ε-caprolactone and polymerizing it, by heating the acrylic polymer to melt it and then mixing it with ε-caprolactone and polymerizing it in that state, and the like.

[0117] During the polymerization of polycaprolactone, some HO-R 3 The diol compound may have a structural unit based on a diol compound represented by the general formula: --OH. Although there is no particular limitation on such a diol compound, for example, a compound having a molecular weight of 500 or less is preferable.

[0118] Specific examples include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, and 1,4-benzenedimethanol.

[0119] When the diol compound is used, the amount of the diol compound used is preferably within the range of 0 to 1% by mass in terms of (diol compound) / (caprolactone+diol compound) (weight ratio). By using the diol compound within such a range, it is particularly preferable in that suitable physical properties can be obtained. The lower limit is more preferably 0.001% by mass, and even more preferably 0.01% by mass. The upper limit is more preferably 0.5% by mass, and even more preferably 0.1% by mass.

[0120] In the polymerization, a catalyst may be used in combination as necessary. Specific examples of the catalyst include tin(II) 2-ethylhexanoate, titanium(IV) tetrabutoxide, zinc bis(2-ethylhexanoate), calcium methoxide, tributyltin methoxide, zinc dibutoxide, and lipase. The amount of the catalyst is preferably 0.001 to 20% by mass. The lower limit is more preferably 0.005% by mass, and even more preferably 0.01% by mass. The upper limit is more preferably 0.5% by mass, and even more preferably 0.1% by mass.

[0121] In the polymer of aspect 2, polycaprolactone is preferably 20 to 90% by mass of the entire polymer. Within this range, the above-mentioned effects can be optimally exhibited. The lower limit is more preferably 30% by mass, and even more preferably 40% by mass. The upper limit is more preferably 80% by mass, and even more preferably 70% by mass.

[0122] (Properties of polymer) The polymer of embodiment 2 of the present invention has the above-mentioned chemical structure, and it is particularly preferable that the polymer has the following physical properties. (molecular weight) The polymer of the present invention preferably has a weight average molecular weight of 5,000 to 2,000,000. The molecular weight is measured according to the method described in the Examples. Specifically, the molecular weight is calculated by measuring the molecular weight by size exclusion chromatography. (Eluent: chloroform, standard sample: polystyrene) (glass transition temperature) The polymer of the present invention preferably has a glass transition temperature of −150 to 150° C. The glass transition temperature is determined from the temperature at which a baseline shift is observed in the first heating process (heating rate: 10° C. / min) by differential scanning calorimetry. (Melting Point) The polymer of the present invention preferably has a melting point of 50 to 250° C. The melting point is measured during the first temperature rise (temperature rise rate of 10° C.) in differential scanning calorimetry. o The melting peak is determined from the temperature at which the melting peak is observed (C / min).

[0123] The polymer of the present invention is not particularly limited in its application, and can be used in molded products such as automobile parts, electrical appliances, agricultural materials, office supplies, and daily necessities, as well as adhesives. EXAMPLES

[0124] The present invention will be specifically described below based on examples, but the present invention is not limited to the following examples.

[0125] The monomers used in the following examples have the following meanings. [ka] In the formula, X=7 TAcγCD-diOH [ka] In the formula, X=7 Ac-γ-CDAAm

[0126] [ka] In the formula, X=6 SH-2-DiOH

[0127] (Example 1 of Aspect 1) (material) TAcγCD-diOH (a compound represented by general formula (2)) was prepared according to the method described in Non-Patent Document 1. α-Thioglycerol, hexamethylene diisocyanate (HDI), dibutyltin diacetate (DBTDA), N,N,N'-tetrakis(2-hydroxyethyl)ethylenediamine (THEED) were purchased from ε-caprolactone (ε-CL), tin(II)bis(2-ethylhexanoate) (Sn(Oct)2), diethylene glycol from Wako Pure Chemical Industries, Ltd. Dry N,N-dimethylformamide (DMF), methanol (MeOH), dichloromethane (DCM), and chloroform-d were from Tokyo Chemical Industry Co., Ltd. Reagents and solvents were used without further purification.

[0128] (measurement) Nuclear magnetic resonance (NMR) spectroscopy: The NMR spectra were measured at 25°C using an ECA-500 NMR spectrometer (JEOL Ltd.) at 500 MHz and 1D. 1 H and 13 C NMR spectra were recorded. In all NMR measurements, chemical shifts were referenced to an internal standard (δ = 0 ppm for tetramethylsilane (TMS)).

[0129] Matrix-assisted laser desorption / ionization time-of-flight mass spectrometry (MALDI-TOF MS) :MALDI measurements were performed using a Bruker autoflex maX LRF with 2,5-dihydroxybenzoic acid as the matrix material. Measurements were operated in reflector mode. TOF-MS measurements were performed using a Bruker autoflex maX LRF with 2,5-dihydroxybenzoic acid as the matrix material. Measurements were operated in reflector mode.

[0130] Tensile test: Tensile tests of the polymers were performed using an Autograph AG-X plus (Shimadzu Corporation) at 25 °C with a deformation rate of 1 mm / s. All samples were tested using at least three specimens to calculate the average values ​​of the mechanical properties and their standard deviations. Young's modulus was calculated from the initial slope of the stress-strain curve in the range of 1-6% strain up to the yield point, and the curve showed a linear increase. Toughness values ​​were calculated as the integral of the stress-strain curve from 0% strain to the fracture strain point. The geometry of the samples used is shown in Figure 45.

[0131] Cyclic Tensile Test: Cyclic tensile tests were performed using an Autograph AG-X plus (Shimadzu Corporation). The specimens were continuously stretched and recovered without intervals, and the maximum strain was set to 200% for 10 times at a deformation rate of 1 mm / s. Cyclic tensile tests at different maximum strains were set to 200%, 400%, 600%, 800%, 1000%, and 1200% at a deformation rate of 1 mm / s. Stress Relaxation Test: Stress relaxation tests were performed using an Autograph AG-X plus. (Shimadzu Corporation). The specimen was stretched to 800%. The strain was then held and the stress was recorded for 3600 seconds.

[0132] Gel Permeation Chromatography (GPC): The number average molecular weight (Mn), weight average molecular weight (Mw) and molecular weight distribution (PDI, Mw / Mn) were measured by GPC using tetrahydrofuran (THF) as the eluent at 40°C, and the molecular weight of the sample was calculated based on a calibration curve using a polystyrene standard. The GPC measurement was performed using THF solvent at 1.50 mL / min. -1The measurement was performed at 40° C. Tosoh HLC-8420GPC EcoSEC (registered trademark, Tosoh) was used for the measurement, and two Tosoh TSKgel columns (TSKgel G2500HHR and TSKgel G4000HHR) were used for the columns.

[0133] Differential Scanning Calorimetry (DSC): The glass transition temperature (Tg) and melting point (Tm) of the samples were measured under N2 gas flow (20 mL / min) using a differential scanning calorimeter (DSC 7020 system manufactured by Hitachi High-Technologies Corporation). Measurements were performed at 10°C / min in the temperature range from -100°C to 100°C. All samples were first cooled to -100°C and then heated to 100°C, and the curves at this stage are called the first scan. After cooling to -100°C again, all samples were heated to 100°C again, and the curves at this stage are called the second scan.

[0134] Thermogravimetric analysis (TGA): The thermal degradation of the polymer was measured by a TGA system (PerkinElmer STA 6000) by increasing the temperature from 80°C to 500°C at a heating rate of 10°C / min under N2 gas flow (20 mL / min).

[0135] ATR-FTIR: Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) was performed using a JASCO FT / IR-6100 spectrometer at 4000–800 cm -1 The measurements were performed in the wavenumber range of

[0136] (Synthesis Example 1) Synthesis of SH-2-DiOH [ka]

[0137] SH-02 (2.14 g, 1 mmol), α-thioglycerol (1.1 g, 10 mmol), and IRGACURE 184 (20 mg, 0.1 mmol) were dissolved in methanol (10 mL). This mixture was irradiated with UV light from a Hg lamp (HL 100 G, HB 100 A-1, Ceritec Co., Ltd., λ = 365 nm) for 2 h. The solution was then dropped into cold water (300 mL) and suction filtered to separate the white precipitate. The resulting solid was dried overnight at 50 °C in a blower dryer and then dried in vacuum at 50 °C for 1 day. The yield is 16% (0.37 g).

[0138] (Synthesis Example 2) Preparation of Aliphatic Polyester Resin

[0139] [ka]

[0140] Diethylene glycol and Sn(Oct) were added to the drying tube under N2. ε-caprolactone was added to the reaction mixture and reacted at 120 °C for 20 h. After the given time, the reaction mixture was directly precipitated into cold hexane to obtain the desired aliphatic polyester (PCL x The ratio of the amounts of the raw materials used is shown in Table 1.

[0141] [Table 1] a 1 The Mn of PCLx-diOH was calculated from H NMR.

[0142] Example 1 Preparation of the polymer 4-1 Preparation of PCLx-γCD(a)-PU

[0143] [ka]

[0144] Before the reaction, the mixture of TAcγCD-diOH and PCLx-diOH was heated at 80°C under vacuum overnight to remove moisture. The mixture of TAcγCD-diOH (a mol%) and PCLx-diOH ((100-a) mol%) was sonicated at 60°C for 30 min and then dissolved in dry DMF. HDI ([NCO] / [OH]=1.05 / 1) and DBTDA (0.25 wt%) dissolved in dry DMF were added to the above mixture. The reaction mixture was heated at 60°C for 24 h under N2. After the specified time, the reaction mixture was precipitated in a cold solvent of DCM / MeOH (v / v=1 / 4) to obtain PCLx-γCD(a)-PU. The raw material feed ratios of each polymer are shown in Table 2. The GPC measurement results are shown in Table 5 and Figure 24.

[0145] [Table 2] X : 1.5k, 2.4k, 3.5k. a : mol% of TAcγCD-diOH.

[0146] Comparative Example 1 4-2 Preparation of lPCLx-PU (Comparative Example without Cyclodextrin Ring)

[0147] [ka]

[0148] Prior to reaction, all raw materials were heated at 80 °C under vacuum overnight to remove moisture. PCLx-diOH was dissolved in dry DMF. HDI ([NCO] / [OH] =1.05 / 1) and DBTDA (0.25 wt%) dissolved in dry DMF were then added. The reaction mixture was heated at 60 °C under N2 for 24 h. After the specified time, the reaction mixture was precipitated in a cold solvent of DCM / MeOH (v / v=1 / 4) to obtain lPCLx-PU. The feed ratios are shown in Table 3. The GPC measurement results are shown in Table 5 and Figure 24.

[0149] [Table 3] x : 1.5k, 2.4k, 3.5k.

[0150] Comparative Example 2 Preparation of PCLx-THEED(b)-PU

[0151] [ka]

[0152] Before the reaction, all the reagents were heated at 80 °C under vacuum overnight to remove moisture. THEED (b mol%) and PCLx-diOH (b mol%) were mixed under ultrasonication at 60 °C for 30 min and then dissolved in dry DMF. HDI ( [NCO] / [OH] =1.05 / 1) and DBTDA (0.25 wt%) dissolved in dry DMF were added to the above mixture. The reaction mixture was heated at 60 °C for 24 h under N2. After the given time, the reaction mixture was precipitated in a cold solvent of DCM / MeOH (v / v=1 / 4) to achieve PCLx-THEED (b)-PU. The feed ratios were listed in Table 4. The GPC measurement results were shown in Table 5 and Figure 23.

[0153] [Table 4] X : 1.5k, 2.4k, 3.5k. b : mol% of THEED.

[0154] The results of GPC measurement of the resins of the above-mentioned Examples and Comparative Examples are shown in Table 5.

[0155] [Table 5]

[0156] Film preparation PCLx-γCD(a)-PU was dissolved in DCM and poured into a Teflon mold. A film was obtained by leaving it at room temperature for 24 h and then at 35 °C overnight under vacuum.

[0157] The FTIR measurement results of the obtained film are shown in Figure 25. From the results of Figure 25, it can be seen that NHCOO- groups and -COO- groups are present, and therefore PCL 2.4k It was revealed that the polymerization of -PU was successful.

[0158] The results of DSC measurement of the obtained polymer are shown in Figure 26. From these results, the thermal properties (particularly the characteristics of the glass transition temperature and melting point) of the polymer of the present invention became clear.

[0159] The relationship between Tg and ΔH obtained by DSC is shown in (a) crosslinking ratio / Tg (b) crosslinking ratio / ΔH. From these results, (a) when crosslinking points were introduced, all crosslinked polymers were PCL. 2.4k It was found that the Tg of the crosslinked polymer was higher than that of the crosslinked polymer of -PU, and the higher the crosslinking amount, the higher the Tg. (b) The introduction of the covalent crosslinker THEED increased ΔH, but the introduction of the mobile crosslinker CD slightly decreased ΔH.

[0160] For each of the polymers of the Examples, the strain-stress curves are shown in Figures 28 and 29. From these results, it is clear that the polymers of the present invention have superior physical properties in both elongation and breaking strength compared to the Comparative Examples.

[0161] The relationship between Young's modulus and toughness for each sample is plotted in Figures 30 and 31. This makes it clear that the polymer of the present invention has excellent performance in both Young's modulus and toughness.

[0162] The hysteresis loss calculated from the cyclic stress-strain curves at a fixed strain (200%) is shown in Figure 32. Ten cycles were performed. The results show that the hysteresis loss of all polymers can be calculated, and that the value tends to stabilize after five cycles.

[0163] The cyclic stress-strain curves for each sample at a fixed strain (200%) are shown in Figure 33. Ten cycles were performed. The results reveal that the hysteresis due to the slippage of molecular chains in the supramolecular network is largest in the first cycle.

[0164] Figure 34 shows (a) the cyclic tensile test curve of PCL-γCD (5-PU recorded with increasing maximum strain. (b) the energy dissipation and damping capacity of each circle of the cyclic tensile test curve. Figure 35 shows (a) the cyclic tensile test curve of PCL-γCD 5-PU recorded with increasing maximum strain, and (b) the energy dissipation and damping capacity of each circle of the cyclic tensile test curve. From these results, (a) the hysteresis loop became larger with increasing strain, and the residual strain became prominent. (b) It was confirmed that the energy loss increased with increasing strain, and the hysteresis loss of the polymer maintained a high value (90% or more). Thus, it was revealed that the polymer had good energy dissipation performance at each strain.

[0165] PCL 2.4 k The stress relaxation time curves of -γCD (2) -PU are shown in Figure 36, and those of PCL 3.5k The stress relaxation time curve of -γCD5-PU is shown in FIG. These results confirmed that the instantaneous stress at 800% strain disappeared within 1 hour in the stress relaxation test, revealing the effective energy dissipation effect due to the sliding ring effect of CDs.

[0166] Recyclability test Methods: After tensile testing, samples were collected and dissolved in DCM at room temperature (25-30°C). The solution was poured into a Teflon mold. Films were obtained by leaving them at room temperature for 24 hours and then at 35°C overnight under vacuum. The toughness measured for the obtained film is shown in Figure 38. Figure 38 shows the measurement results for Young's modulus of the original film (n=1), the film after the first recycling (n=2), and the film after the second recycling (n=3). The results in Figure 38 make it clear that the resin performance does not decrease significantly even in the recycled resin.

[0167] (Enzymatic decomposition reaction) The PCL-γCD 9-PU obtained by the above-mentioned method was subjected to an enzymatic decomposition reaction. In the decomposition experiment, 50 mg of PCL-γCD 9-PU was dissolved in toluene containing 5 wt % water, and 40 wt % of lipase (manufactured by Novozyme) was added. This solution was reacted at 60°C under a nitrogen stream. Samples were taken before the reaction, 12 hours, 24 hours, and 84 hours after the start of the reaction, and the molecular weights of these were measured by GPC. The results are shown in Figure 39. From this result, it became clear that the polymer of the present invention is decomposed by enzymes, and therefore has a small environmental impact.

[0168] (Enzymatic polymerization reaction) The PCL-γCD 9-PU obtained by the above-mentioned method was subjected to an enzymatic polymerization reaction. In the decomposition experiment, 50 mg of PCL-γCD 9-PU was dissolved in anhydrous toluene, and 40% by weight of lipase (manufactured by Novozyme) was added. This solution was reacted at 60°C under a nitrogen stream. Samples were taken before the reaction, and 12 hours, 24 hours, 36 hours, and 48 hours after the start of the reaction, and the molecular weights of these samples were measured by GPC. The results are shown in Figure 40. From these results, it became clear that the polymer of the present invention can be further polymerized by the enzyme. Therefore, it is possible to re-polymerize the polymer recovered by decomposing it into a low molecular weight by the above-mentioned decomposition reaction and reuse it. From this point of view, it became clear that the polymer has a small environmental impact.

[0169] (Relationship with reaction time of enzymatic polymerization reaction) The polymer was dissolved in dry toluene with molecular sieves and Novozym 435 (wt % relative to the polymer) was added. The reaction was carried out at 60 °C under N2. At each reaction time (1 h, 2 h, 4 h, 8 h, 12 h, 24 h, 36 h, 48 h, 72 h, 96 h, 120 h), the reaction solvent was collected for GPC measurement. Such experiments were carried out for PCL3.5k-γCD(9)-PU, PCL3.5k-γCD(5)-PU, and lPCL3.5k-PU. The results are shown in Figure 41. (a) is 10% by mass of enzyme, (b) is 20% by mass of enzyme, and (c) is 50% by mass of enzyme.

[0170] In Figure 41(a), the Mn of PCL3.5k-γCD(9)-PU changes little. In Figure 41(b), the Mn of PCL3.5k-γCD(9)-PU began to decrease after 1 hour and reached a minimum after 12 hours. The Mn of PCL3.5k-PU without mobile crosslinks hardly changed. In Figure 41(c), Mn of PCL3.5k-γCD(9)-PU continued to increase within 8 hours and then began to decrease. Mn of PCL3.5k-γCD(5)-PU continued to increase within 96 hours. Mn of lPCL3.5k-PU hardly changed even after 120 hours.

[0171] These experimental results clearly show that the decomposition or increase in molecular weight of PCL3.5k-γCD(a)-PU can be controlled by changing the amount of enzyme added.

[0172] (Example 2 of Aspect 1) [ka] Before the reaction, the mixture of SH-2-DiOH and PCLx-diOH was heated at 80 °C under vacuum overnight to remove moisture. The mixture of SH-2-DiOH (a mol%) and PCLx-diOH ((100-a) mol%) was sonicated at 60 °C for 30 min to 1 h, and then dissolved in dry DMF. HDI ([NCO] / [OH] = 1.05 / 1) and DBTDA (0.25 wt%) dissolved in dry DMF were added to the above mixture. The reaction mixture was heated at 60 °C for 24 h under N2. After the specified time, the reaction mixture was precipitated in a cold solvent of DCM / MeOH (v / v=1 / 4) to obtain PCLx-βCD(a)-PU. The raw material feed ratios of each polymer are shown in Table 6. The GPC measurement results are shown in Table 6 and Figure 24.

[0173] The polymer obtained by the above method was subjected to molecular weight measurement, and the results are shown in Table 6.

[0174] [Table 6]

[0175] The resin obtained in the above (Example 2 of Aspect 1) was subjected to the same evaluation test as in (Example 1 of Aspect 1). The results are shown in Figures 42 and 43.

[0176] The results in these figures show that the PCL-PU exhibits higher elongation and breaking strength than the PCL-PU without cyclodextrin. In particular, the PCL-PU exhibits higher elongation and breaking strength even at a relatively low molar ratio of cyclodextrin, and as a result, it exhibits very high toughness. This makes it clear that in embodiment 1, the physical properties differ depending on the difference in resin structure, and that by using these appropriately depending on the purpose, the polymer of the present invention can be used in a wide range of applications.

[0177] (Example of embodiment 2) reagent All reagents were purchased and used without purification. (1) Ethyl acrylate (EA) (Tokyo Chemical Industry Co., Ltd.) (2) Acetylated γ-cyclodextrin-acrylamide (Ac-γ-CDAAm) (Yushiro Chemical Industry Co., Ltd., Kyoeisha Chemical Co., Ltd.) (3) 1-Hydroxycyclohexyl phenyl ketone (Irgacure 184) (Tokyo Chemical Industry Co., Ltd.) (4) ε-caprolactone (CL) (Tokyo Chemical Industry Co., Ltd.) (5) Ethylene glycol (FUJIFILM Wako Pure Chemical Industries, Ltd.) (6) Tin 2-ethylhexyl ester II (Sn(Oct)2) (FUJIFILM Wako Pure Chemical Industries, Ltd.) (7) Deuterochloroform (FUJIFILM Wako Pure Chemical Industries, Ltd.) (8) Chloroform (FUJIFILM Wako Pure Chemical Industries, Ltd.) Measuring Equipment 1 H NMR Nuclear magnetic resonance measurement device "JNM-ECS400 (400 MHz)" (solvent: CDCl3) manufactured by JEOL Ltd., SEC size exclusion chromatography "HLC-8420GPC" (solvent: chloroform, standard sample: polystyrene, column: TSKgel GMHHR-M, guard column: TSKgel guardcolumn HHR-L) manufactured by Tosoh Corporation, tensile testing machine "Small tabletop testing machine EZ Graph" manufactured by Shimadzu Corporation, test conditions: load cell 10N, test speed 10mm / min

[0178] (Synthesis Example 3) Synthesis of MC elastomer [ka]

[0179] An MC elastomer with a network formed by mobile crosslinks was synthesized according to the method described in NPG Asi Mater., 2022, 14, 1. EA (2.3 g, 23 mmol) was placed in a sample tube, Ac-γ-CDAAm (0.55 g, 0.23 mmol) and Irgacure184 (9.6 mg, 0.047 mmol) were dissolved, and the solution was stirred for 60 minutes by ultrasonic vibration. The solution was transferred to a mold and reacted by irradiating ultraviolet light for 30 minutes while cooling on ice. The obtained elastomer was transferred to a Teflon (registered trademark) petri dish and dried under reduced pressure at 80°C for 12 hours in a vacuum heat dryer to remove unreacted monomers.

[0180] MC elastomers were prepared by varying the amount of Ac-γ-CDAAm introduced to 1.0, 2.0, or 3.0 mol %, as shown in Table 7 below.

[0181] [Table 7]

[0182] A colorless and transparent elastomer was obtained by synthesizing MC elastomer. 1 H NMR measurements showed that the MC elastomer had characteristic peaks derived from the acetyl group of Ac-γ-CDAAm, and that the peaks derived from the vinyl group had disappeared, confirming that the synthesis of the MC elastomer had progressed. Comparing the integral values ​​of the peaks of the acetyl group of γ-CD and the peaks due to the terminal ethyl group, the introduction rate of γ-CD was 0.88% for pEAγCD_1 and 2.0% for pEAγCD_2.

[0183] Example 2 A catalyst solution was prepared by dissolving Sn(Oct)2 (0.18g, 0.44mmol) in a sample tube and placing ε-caprolactone (1.1g, 1mL) in the sample tube. In addition, caprolactone (5.4g, 5mL) was placed in the sample tube and ethylene glycol (0.17g, 2.7mmol) was added to prepare an initiator solution. ε-caprolactone (0.60g) was placed in a ground test tube and 12μL each of the catalyst solution and initiator solution were added and stirred. MC elastomer (0.60g) was added to this and stirred well to swell the MC elastomer with the solution. The test tube was sealed with a silicon septum and the inside was replaced with nitrogen. The test tube was then heated at 110 oC for 48 hours to polymerize CL and introduce PCL polymer chains into the MC elastomer. The type of MC elastomer and the amount of PCL introduced were changed and samples were prepared as follows.

[0184] [ka]

[0185] [Table 8]

[0186] The polymer obtained turned white as the amount of polycaprolactone introduced increased. 1 1 H NMR measurement revealed a peak derived from polycaprolactone, confirming that polycaprolactone had been introduced (FIG. 47).

[0187] Size exclusion chromatography (SEC) was used to investigate the molecular weight of the introduced polycaprolactone. Chloroform was used as the mobile phase, and polystyrene was used as the standard sample. A single elution peak appeared for the MC elastomer, whereas a new peak appeared on the low molecular weight side for the mobile crosslinked network material. Comparing the two, the peak on the low molecular weight side is considered to be the elution peak of the introduced PCL (Figure 48). The number average molecular weight of PCL in the material prepared using pEAγCD_1 was approximately 10,000. On the other hand, a decrease in the molecular weight of PCL was observed with pEAγCD_3. This is considered to be the result of the increase in the number of crosslinking points as the amount of γ-CD introduced increases, and the network structure of the MC elastomer becomes denser, inhibiting the polymerization of CL (Table 9).

[0188] [Table 9]

[0189] (Comparative Example 2) Preparation of a material by simply mixing two types of resin PCL was synthesized independently using the above reaction. A simple mixture of this polycaprolactone and MC elastomer (pEAγCD1_PCL50_M) was prepared by the casting method. PCL (0.50 g) and pEAγCD_1 (0.50 g) were placed in a ground test tube. Chloroform (9.0 g) was added and stirred to completely dissolve PCL and pEAγCD_1. The solution was poured into a Teflon (registered trademark) petri dish and heated in an oven at 50 °C for 24 hours to remove the chloroform.

[0190] Comparing pEAγCD1_PCL50 prepared by in situ polymerization with pEAγCD1_PCL50_M prepared by simple mixing, pEAγCD1_PCL50 became a homogeneous material with high transparency, whereas pEAγCD1_PCL50_M became a material with a non-uniform appearance. This is thought to be because pEAγCD1_PCL50 forms a dense network in which the polymer chains of polycaprolactone penetrate into the mobile crosslinked network of the MC elastomer, whereas pEAγCD1_PCL50_M forms less of such a network.

[0191] (molding) The prepared MC elastomer and materials were molded into a film with a thickness of about 300 μm by heat pressing. The heat pressing was performed as shown in Figure 44, with a pressure of 20 MPa and a temperature of 80°C. After heat pressing, the sample was cooled on ice.

[0192] (Mechanical property evaluation) The mechanical properties of the MC elastomer and the prepared mobile crosslinked network material were evaluated by tensile tests. The film-shaped sample was cut with a cutter to prepare test pieces as shown in Figure 45. A tensile test was performed using a 10N load cell at a tensile speed of 10 mm per minute.

[0193] Figure 49 shows the results of tensile tests of MC elastomer and mobile crosslinked network material. As the amount of γ-CD introduced increased, the breaking strain of the MC elastomer decreased and the maximum stress tended to increase (Figure 49a). This is thought to be due to the effect of increasing the crosslink density in addition to the molecular rigidity of γ-CD itself. 50wt% polycaprolactone was introduced into the MC elastomer.

[0194] Comparing the mechanical properties of pEAγCD1_PCL50, pEAγCD2_PCL50, and pEAγCD3_PCL50, pEAγCD1_PCL50 showed the largest values ​​for both the breaking strain and maximum stress. When evaluating the toughness and initial modulus of the MC elastomer and the prepared material, pEAγCD1_PCL50 showed the largest improvement in properties in both toughness and initial modulus. This is thought to be due to the introduction of PCL, a molecular chain with relatively high rigidity, into the network. In pEAγCD3_PCL50, the breaking strain increased, resulting in improved toughness (Figure 49b). This is thought to be due to the intrusion of polycaprolactone polymer chains into the network of pEAγCD_3, which has a high crosslink density, expanding the network and improving the flexibility of the material.

[0195] For pEAγCD_1, which showed the greatest improvement in properties, we investigated the mechanical properties when the amount of PCL introduced was changed. As a result, improvements in toughness and initial modulus were observed at all introduction rates. (Figure 49a) However, pEAγCD1_PCL80 became a brittle material, and it was difficult to prepare test specimens. pEAγCD1_PCL50, in which 50 wt% PCL was introduced, showed the greatest improvement in mechanical properties, with the initial modulus increasing by about 70 times and the toughness increasing by about 3.5 times. At introduction rates higher than this, the improvement remained constant (Figure 49b).

[0196] This is thought to be due to the fact that the mobile crosslink network of the MC elastomer expands when the MC elastomer is immersed in an ε-caprolactone solution during synthesis. If the volume of the ε-caprolactone solution increases, the mobile crosslink network of the MC elastomer may expand significantly, leading to collapse. Previous studies have also reported that when a material with mobile crosslinks is immersed in a solution, polymer chains may escape from the γ-CD rings. Due to the above factors, the network expanded greatly in pEAγCD1_PCL60 and pEAγCD1_PCL70, limiting the improvement of mechanical properties, but in pEAγCD1_PCL50, the introduction of polycaprolactone occurred while maintaining the network of the MC elastomer, leading to improved mechanical properties.

[0197] The mechanical properties of pEAγCD1_PCL50, prepared by in situ polymerization, and pEAγCD1_PCL50_M, obtained by simple mixing, were also compared in the same manner. Although pEAγCD1_PCL50_M showed an improvement in the initial modulus, it showed almost the same results as the MC elastomer pEAγCD_1, and did not show any significant improvement in properties (Figure 51b). This result revealed that the mechanical properties were improved by introducing polycaprolactone into the MC elastomer with a mobile crosslinked network to form semi-IPNs.

[0198] From the above results, the following facts became clear. (1) The mechanical properties of the MC elastomers changed with increasing the amount of γ-CD introduced, which is believed to be due to an increase in the density of crosslinks. (2) pEAγCD_1, which showed the largest breaking strain among the MC elastomers, showed an improvement in the initial modulus of elasticity and the associated toughness increase by the introduction of polycaprolactone. The greatest improvement in properties was observed when the amount of polycaprolactone introduced was 50 wt%, with the initial modulus of elasticity increasing by about 70 times and toughness increasing by about 3.5 times. (3) Comparing pEAγCD_PCL50, which was prepared by polymerization of ε-caprolactone in the presence of MC elastomer, and pEAγCD1_PCL50_M, which was prepared by simple mixing, pEAγCD_PCL50 was a material with a uniform appearance, while pEAγCD_PCL50_M was a material with a non-uniform appearance. In addition, the improvement in mechanical properties of pEAγCD_PCL50_M due to the introduction of polycaprolactone was limited.

[0199] These results demonstrated that the introduction of polycaprolactone polymer chains into a mobile crosslinked network of MC elastomers by in situ polymerization to construct semi-IPNs leads to improved mechanical properties of the material. [Industrial Applicability]

[0200] The polymer of the present disclosure has a low environmental impact because it uses an aliphatic polyester resin, while having excellent physical properties, and therefore can be used in many fields where such performance is required.

Claims

[Claim 1] A compound having a structure represented by the following general formula (11): 【Chemistry 1】 (In the formula, R 1 teeth, (A) The following general formula (12): -R 3 -NH-R 4 (12) (R 3 is an alkylene group having 3 to 20 carbon atoms, which may be linear or branched and may have a substituent. R 4 is a structure represented by the following formula: 【Chemistry 2】 In the formula, R 10 represents hydrogen or a methyl group. (a) The following general formula (13): -R 5 -NHGNH-R 6 (13) (R 5 is an alkylene group having 3 to 20 carbon atoms, which may be linear or branched and may have a substituent. R 6 is the above R 4 Same as or (c) a compound represented by the following general formula (14): -R 5 -OCONH-R 6 (14) (R 5 and R 6 is the same as above.) It represents one of the following. R 2 represents a hydrogen atom, an acyl group having 2 to 50 carbon atoms, or an alkyl group having 1 to 30 carbon atoms. R c represents a group represented by the following general formula (1). 【Chemistry 3】 (In the formula, R 1 are the same or different and each represents an acyl group having 2 to 50 carbon atoms, an alkyl group having 1 to 30 carbon atoms, or -CONHR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and R 1 At least 20% of the groups are acyl groups having 2 to 50 carbon atoms, alkyl groups having 1 to 30 carbon atoms, or -CONHR. 2 It is one of them. x is an integer from 5 to 7)

Citation Information

Patent Citations

  • Polymer material and its manufacturing method

    JP6624660B1

  • Cyclodextrin derivative having polymerizable unsaturated group

    WO2022024908A1

  • Host group-containing polymerizable monomer, polymer material, and method for manufacturing same

    WO2023026980A1

  • Polyurethane urea resin composition and method for producing the same

    JP2019203082A